2014
DOI: 10.1111/ijag.12069
|View full text |Cite
|
Sign up to set email alerts
|

Glass–Ceramic Foams from Borosilicate Glass Waste

Abstract: In this study, we reported the studies on a glass-ceramic foam with wollastonite and cristobalite micrometric crystals prepared by sintering a borosilicate glass waste with organic binder as foaming agent. The waste glass, coming from the dismantling of washing machine, was characterized by high CaO content and low-temperature sinterability. The effect of the temperature on the sinter-crystallization ability of the borosilicate glass waste was followed with thermal analysis, heating microscopy, and electron sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
1
36
0
3
Order By: Relevance
“…A cristobalita é uma fase polimórfica do quartzo e é geralmente observada em vidros sódico-cálcicos que sofreram devitrificação. A transformação da fase cristobalita α para a forma β ocorre a 200 o C e é acompanhada de grande variação de volume, o que geralmente compromete a resistência mecânica devido à formação de micro-trincas [5] nos materiais. Apesar disto, não foram observadas micro-trincas nas espumas vítreas obtidas.…”
Section: Figuraunclassified
See 1 more Smart Citation
“…A cristobalita é uma fase polimórfica do quartzo e é geralmente observada em vidros sódico-cálcicos que sofreram devitrificação. A transformação da fase cristobalita α para a forma β ocorre a 200 o C e é acompanhada de grande variação de volume, o que geralmente compromete a resistência mecânica devido à formação de micro-trincas [5] nos materiais. Apesar disto, não foram observadas micro-trincas nas espumas vítreas obtidas.…”
Section: Figuraunclassified
“…Dentre os materiais normalmente utilizados para a obtenção de materiais porosos, pode-se mencionar a alumina, mulita, carbeto de silício, zircônia e hidroxiapatita e também materiais vítreos ou parcialmente cristalinos, como os vidros e os vitrocerâmicos [2,4,5,6]. Em tais casos, o uso de resíduos provenientes da reciclagem de vidro em geral ou de indústrias cerâmicas é uma possibilidade a ser explorada, pois a reciclagem e reutilização do vidro contribuem para a matriz energética nacional com a economia de grande quantidade de energia.…”
unclassified
“…This explains the continuous increase of interest of researchers and governments in this class of materials especially the low cost ones that are produced with a lower energy consumption and that may contribute to the management of some natural or/and industrial wastes [1,2]. Recent studies have proposed in this direction porous inorganic polymer matrices from clays [3,4] or wastes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the corrosion of pure aluminum in alkaline solution proceeds mainly by water reduction according to (Eqs. (1) and 2): the dissolution rate depending on the concentration of OH À and aluminate ions Al(OH) 4 À at the solid/ liquid interface. It was concluded that the process of the corrosion of aluminum can be used for the production of porous geopolymers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative energy‐saving approach, the methods of production of lightweight building materials without preliminary glass preparation have been developing extensively. The typical raw materials used in these methods are waste products such as various ashes and washing aggregate sludge . Disadvantages of such methods are high bulk density (>1 g/cm 3 ) of resulting lightweight material and high sintering temperature (>1000°C).…”
Section: Introductionmentioning
confidence: 99%